Lifetime seismic resilience of aging bridges and road networks. Issue 2 (1st February 2020) - Capacci, Luca; Biondini, Fabio; Titi, Andrea
Abstract: The performance of lifelines under damage and emergency conditions induced by sudden extreme events, such as earthquakes, can be assessed based on the concept of resilience. Damage also arises in time due to aging, affecting the structural performance of each network component and, consequently, impairing the overall system functionality. Furthermore, the sparse location over the network of vulnerable deteriorating structures, such as spatially distributed bridges, should be taken into account to establish proper infrastructure management policies. In this article, a probabilistic approach is proposed to assess the seismic performance of transportation networks considering the uncertainties involved in the lifetime structural response of aging bridges under different earthquake scenarios. The time-variant seismic capacity associated with prescribed limit states is evaluated by nonlinear incremental dynamic analysis. The initial damage induced by seismic events and its recovery process through structural repair is related to traffic restrictions to different road users. Traffic flow distribution analyses are carried out over the road network to assess the post-event system functionality and the corresponding seismic resilience. The role of different factors such as aging, earthquake scenario, and seismic capacity correlation is investigated by considering spatially distributed reinforced concrete bridges exposed to corrosion and highway networks with detours and re-entry links.